Digital humanities for librarians - Wilson, Emma (Rowman & Littlefield, 2051)
Digital Humanities For Librarians is a one-stop resource for librarians and LIS students working in this growing area of academic librarianship. The broad overview is followed by a series of intensely practical chapters answering questions with step-by-step approaches to both the digital and the human elements of Digital Humanities librarianship. Intro – Contents – Preface – Acknowledgments – Part I. What IsDigital Humanities? – Ch01. What Is Digital Humanities? – Ch02. Who Is Doing Digital Humanities? – Ch03. Library Models for Supporting Digital Humanities – Part II. The Digital Part of Digital Humanities – Ch04. Metadata for Digital Humanities – Ch05. Creating Digital Exhibitions, Archives, and Databases – Ch06. Text Encoding with the Text Encoding Initiative (TEI) and the Music Encoding Initiative (MEI) – Ch07. Digital Mapping – Ch08. Computational Text Analysis – or, Big Data for Digital Humanities – Part III. The Human Part of Digital Humanities – Ch09. Outreach for Digital Humanities – Ch10. Who Is on My Team? – Ch11. Project Management for Digital Humanities – Ch12. Managing Humans in Digital Humanities Projects – Ch13. Managing Data in Digital Humanities Projects – Bibliography – Index – About the Author.
Keywords: Humanities; Academic libraries; Library outreach programs; Libraries; Metadata; Electronic books